EFFECTS OF HEALTH EDUCATION ON KNOWLEDGE ABOUT BREAST SELF EXAMINATION (BSE) AGE WOMEN IN FERTILE IN DK KIJON - STIKES DUTAGAMA KLATEN (STIKES DUTAGAMA KLATEN, 2014)
Background: Due to the lack of appropriate and adequate information on the breast self-examination, the students cannot make early detection on the breast cancer. It has been acknowledged that breast cancer is one of the cancers that cause the high death rate in women after cervical cancer. Objective: The general objective of the research is to investigate the effect of the health education of breast self-examination on the knowledge of the womant. The specific objectives of the research are: (1) investigate the difference of knowledge between the womant who are not taught with health education and those who are taught with health education, both prior to and following the treatment; (2) to analyze the effect of health education of breast self examination on the of the womant. Method: The research used a quasi experiment with a cross-sectional research design. It was conducted at kojon village. The data of the research were gathered through tests (pre-and post-tests), and questionnaire of Liket’s scale. The data were analyzed by using a two-way analysis of variance (ANOVA). Result: The results of the research show that (1) there is an effect of the health education of breast self-examination on the knowledge of the womant as indicated by the value of p = 0.999 in the pre-test and that of p = 1.000 in the post test following the treatment; and (2) there is an effect of the health education of breast self-examination on the attitude of the womant as indicated by the value of p = 0.999 in the pre-test and that of p = 1.000 in the post test following the treatment womant in the kojon village.